DETERMINANTS FOR THE DECLINE IN HINDI LANGUAGE STUDENTS IN FIJI NATIONAL UNIVERSITY - Goundar, Prashneel Ravisan; Prasad, Preetika A. (International Journal of Research -GRANTHAALAYAH, 2017)
In Fiji, the Hindi language is one of the three National languages (English and I-Taukei) used. It is the mother tongue of almost 35% of Fiji’s population attested to the arrival of indentured laborers in the late 1800’s which give the country multilingualism. Fiji was previously bilingual with the colonialism, Christian missionaries and explorers bringing the English language. Unfortunately, there is emerging a trend in the decline of tertiary students undertaking studies in the Hindi Language. This paper evaluates the determinants for the decline in Hindi Language students and makes appropriate recommendations.